Pressureless sintering of electro-conductive zirconia composites - Amiriyan, M.; Singh, R.; Sopyan, I.; Satgunam, M.; Tolouei, R.; Dung, T.W. (Engineering, 2011)
In the present work, 3 mol Yttria-stabilized tetragonal zirconia (Y-TZP) composite containing 25 wt. of zirconium diboride (ZrB2) was prepared via pressureless sintering method in an inert atmosphere over the temperature range of 1350-1550 degrees C for one hour. The effect of zirconium diboride content in the zirconia matrix, as well as the sintering temperature on densification, phase stability and electrical properties of sintered samples have been studied. The results revealed that there was a significant increased in electrical conductivity of sintered samples when 25 wt. of ZrB2 is incorporated into Y-TZP matrix.